The Effect of Instructional Media “DAPACA” to Improve Reading Skills for Students with Learning Disability - Gustian, Rizky; Tarsidi, Iding (Journal of Education for Sustainability and Diversity, 2023)
This research developed Instructional Media for student’s with learning disability using media "DAPACA". The purpose of this study was to improve the ability of beginning reading with DAPACA media, DAPACA media is designed using several arrays of syllable cards when put together can make a word and sentence, the subject of this research is 5 student’s with learning disability specific to early reading skills. The research method used in this study uses an experimental method using a single group design pre-test post-test. The data collection technique used in this study was a test. The test given in the form of an instrument of early reading skills. Data collection techniques are carried out during the session Pre-test and Post-test. The results showed that DAPACA instructional media can improve early reading skills, can be seen with the results of the acquisition of the average ability score for the pre-test results is 78 and The average for the post-test results is 112, there was an increase in the score of 34.